Studies on the Variation of the Genus Dryas in Greenland. - Elkington, T.T. (Meddelelser om Grønland, 1965)
A short history of the taxonomic treatment of the genus Dryas in Greenland is given, stressing the difficulties which have arisen in N. and E. Greenland. Studies of morphological characters using herbarium material and pressed random samples are described. The most useful characters in the study of Greenland material are presence or absence of branched hairs on the leaves, leaf crenation, and to a lesser extent ratio of leaf width at the middle of the leaf to that at the base. These studies also show that some Greenland specimens, which have been assigned to several taxa, are referable to either D. integrifolia VAHL, D. octopetala L. or hybrids between these two species. The previous reports of D. crenulata JUZ. are argued to be large leaved, ecological variants of D. octopetala and hybrids of this species with D. integrifolia; those of D. punctata JUZ. and D. hookeriana JUZ. to be variants within the variation of D. octopetala. A herbarium survey of the genus shows that all specimens from S.E. and W. Greenland can be referred to D. integrifolia, and those from N.W., N. and E. Greenland to D. integrifolia, D. octopetala and intermediates. One of these intermediate types has previously been called D. chamissonis SPRENG., but this name is shown to have never been validly published. A field investigation in the Kong Oscars Fjord region, E. Greenland (lat. 72° N.), measuring populations in the field and collecting population samples shows that all populations contain intermediate types and have the characteristics expected of introgressive hybridization between D. integrifolia and D. octopetala. Floristic lists and soil analyses are given from the localities sampled. These show that variation in population structure is not correlated with any particular vegetation type or soil conditions. Cytological studies on field material show meiosis to be almost completely regular with n = 9. The described variation is discussed and interpreted as an example of allopatric introgression over a very large area. The question of experimental and formal taxonomic categories is commented upon and it is concluded that it is best to regard D. octopetala and D. integrifolia as incipient ecospecies and of specific status.